Influence of Compositional Gradient Effect on Tight Condensate Gas Reservoir Development - Jing Chen; Xinmin Song; Baozhu Li; Xiaoli Luo; Youjing Wang; Jinfang Wang (Geofluids)
Condensate gas is a transition fluid between oil and gas, which is sensitive to the reservoir temperature and pressure. In condensate gas reservoir, especially in the moderate-giant one, fluid composition often varies with depth. This phenomenon has important influences on development. Anisothermal compositional gradient theory is used to analyze the main factors influencing the compositional gradient distribution to understand the basic regularities of the compositional variation with depth. Geothermal gradient, fluid composition, reservoir temperature, and reservoir pressure will affect the compositional gradient, of which geothermal gradient has the most direct and obvious influence. Furthermore, fluid model with compositional gradient was built in a tight condensate gas reservoir of the Middle East, and the influence of compositional gradient on dynamic performance is evaluated. The results show that the compositional gradient has a significant influence on the original gas in place, development strategy, central processing facilities, and so on. Therefore, compositional gradient requires more attention while exploiting moderate-giant condensate gas reservoirs in order to achieve more economical benefits.